Risk Management Practices in Construction A Global View - Oke, Ayodeji E.; Adetoro, Pelumi E.; Stephen, Seyi S.; Aigbavboa, Clinton O.; Oyewobi, Lukman O.; Aghimien, Douglas O. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This volume describes risk management practices in the construction industry in selected countries, with an emphasis on developing countries and how these countries can learn from the practices in more developed ones. Risk management in the construction industry can be difficult to understand due to the various complex procedures that are involved and to the unique concerns and contexts associated with each project. The industry has been a key contributor to the economic and social development of many countries of the world and is increasingly incorporating sustainability into its practices. However it is plagued by various risks that can affect the quality, cost, time and overall sustainability of projects. Therefore, there is need to effectively manage risk in order to ensure timely completion of construction projects in good quality and within budget, which in turn results in more efficient and often more sustainable practices. The book is divided into four parts. The first section features a primer on risk management practices as they pertain to the construction industry. The second part dives in to describe risk management in selected developing countries, including Malaysia, Qatar, Saudi-Arabia, South Africa, Sri-Lanka and Tanzania, as well as the city of Hong Kong. The third section describes the construction risk management practices of a selection of more developed countries with known risk management institutes and established practices of risk management. These countries include Australia, Canada, Sweden and United States of America. The fourth part offers a general overview of the definition, concepts and process of risk management based on reviewed literature. It also discusses the benefits of effective risk management to clients and to project teams, especially from the perspective of ensuring sustainability. This last section also summarizes the risk management practices in both developing and developed countries for the purpose of improving the practices in the former by learning from the latter.
Chapter 1. General Introduction -- Chapter 2. Risk Management Practices in Malaysia -- Chapter 3. Risk Management Practices in Nigeria -- Chapter 4. Risk Management Practices in Qatar -- Chapter 5. Risk Management Practice in Saudi Arabia -- Chapter 6. Risk Management Practices in South Africa -- chapter 7. Risk Management Practices in Sri Lanka -- Chapter 8. Risk Management Practices in Tanzania -- Chapter 9. Risk Management Practices in Australia -- Chapter 10. Risk Management Practices in Canada -- Chapter 11. Risk Management Practices in Sweden -- Chapter 12. Risk Management Practices in the United States of America. Chapter 13. General Summary on Risk Management.
Keywords: Financial risk management; Construction industry -- Management; Sustainability; Civil engineering; Risk Management; Construction Management; Sustainability; Civil Engineering